Antibiotic Use in Children with Acute Respiratory or Ear Infections: Prospective Observational Comparison of Anthroposophic and Conventional Treatment under Routine Primary Care Conditions. (17th November 2014) - Hamre, Harald J.; Glockmann, Anja; Schwarz, Reinhard; Riley, David S.; Baars, Erik W.; Kiene, Helmut; Kienle, Gunver S.
Abstract : Children with acute respiratory or ear infections (RTI/OM) are often unnecessarily prescribed antibiotics. Antibiotic resistance is a major public health problem and antibiotic prescription for RTI/OM should be reduced. Anthroposophic treatment of RTI/OM includes anthroposophic medications, nonmedication therapy and if necessary also antibiotics. This secondary analysis from an observational study comprised 529 children <18 years from Europe (AT, DE, NL, and UK) or USA, whose caregivers had chosen to consult physicians offering anthroposophic (A-) or conventional (C-) treatment for RTI/OM. During the 28-day follow-up antibiotics were prescribed to 5.5% of A-patients and 25.6% of C-patients (P < 0.001 ); unadjusted odds ratio for nonprescription in A- versus C-patients 6.58 (95%-CI 3.45–12.56); after adjustment for demographics and morbidity 6.33 (3.17–12.64). Antibiotic prescription rates in recent observational studies with similar patients in similar settings, ranged from 31.0% to 84.1%. Compared to C-patients, A-patients also had much lower use of analgesics, somewhat quicker symptom resolution, and higher caregiver satisfaction. Adverse drug reactions were infrequent (2.3% in both groups) and not serious. Limitation was that results apply to children of caregivers who consult A-physicians. One cannot infer to what extent antibiotics might be avoided in children who usually receive C-treatment, if they were offered A-treatment.